The Impact of EndoAnchor Penetration on Endograft Structure: First Report of Explant Analysis - Jonathan Grandhomme (EJVES Vascular Forum, 2020)
Objective: The adjunctive use of Heli-FX EndoAnchors (EAs) in endovascular aneurysm repair has been proposed for the treatment or prevention of type Ia endoleaks. The aim of this study was to evaluate the impact of the penetration of EAs on endograft textile structure from two aortic endografts that had been explanted for persistent type Ia endoleak despite the implantation of EAs. Methods: An Aorfix aortic endograft was implanted in an 85 year old man. Six months later, six EAs were implanted for Ia endoleak. The endograft was explanted as an emergency seven months later for aneurysm rupture. An Endurant II aortic endograft was implanted in an 80 year old man. Seven EAs were implanted 24 months later for type Ia endoleak. A proximal cuff extension with bilateral renal and superior mesenteric artery chimneys was performed 18 months later to treat a persistent type Ia endoleak. Endograft explantation was performed six months later owing to persistent type Ia endoleak and aneurysm sac enlargement. Explant analysis in both cases was performed at GEPROVAS. Results: Systematic analysis of both explants, including the 13 EAs, revealed the following lesions: (1) alteration of textile structure directly linked to several penetrations of the fabric with the same EA and tears of the textile fibres in two cases; (2) tears of the binding threads as the EA had passed through them in five cases; and (3) interactions between EA and endograft stents in four cases. Conclusion: The site of EA penetration into the endograft might contribute to endograft fabric damage and to a loss of stability of the endograft at the level of the aortic neck.